The Influence of Discipline and Integrity on Employee Performance at the Regional Financial and Asset Management Agency of Arfak Mountains Regency - Betty Mayor; Mariana Salosso (STIE Amkop Makassar, 2025)
This research analyzes the effect of discipline and integrity on employee performance at the Regional Financial and Asset Management Agency (BPKAD) of Arfak Mountains Regency. In an era of government that emphasizes good governance, the performance of the state civil apparatus (ASN) is in the spotlight. BPKAD, an agency responsible for managing regional finances and assets, is required to have optimal performance. Discipline and integrity are believed to be important foundations in realizing the expected performance. This study aims to empirically examine the extent to which discipline and integrity affect employee performance at BPKAD of Arfak Mountains Regency. This research uses a quantitative approach with a survey method. The questionnaire was distributed to all BPKAD employees who became the research sample. The collected data were analyzed using multiple linear regression techniques to test the research hypothesis. The results of the study are expected to make a significant contribution to the development of human resource management (HRM) in the local government environment, especially in terms of increasing discipline and integrity to achieve better performance. In addition, this research is also expected to provide practical implications for BPKAD leaders in formulating effective policies and programs to improve employee discipline and integrity and to improve the effectiveness of regional financial and asset management. This research also considers the geographical and socio-cultural context of Arfak Mountains Regency that may affect the implementation of discipline and integrity in the work environment. Keywords: Discipline, Integrity, Employee Performance, Governance, Organisation